ROLE OF EMOTIONAL INTELLIGENCE IN FACILITATING INTERPERSONAL COMMUNICATION AND STRENGTHENING RELATIONSHIP - Sunny, Sanjay; Dr.M.Salathiyan (The journal of contemporary issues in business and government, 2022)
Higher emotional intelligence is necessary for both managers and employees in an organisation because it helps all the individuals in an organisation to control individual emotions in operation management activities. This emotional intelligence is necessary because it brings flexibility and reduces the chances of workplace stress. As a result, the individuals can understand the situations of other individuals in the workplace quite effectively. This is necessary to maintain a friendly and peaceful workplace environment. Strong emotional intelligence not only facilitates good communication approach, but also helps organisations to maintain strong relationship between the management professionals and employees of an organisation.